Autosomal Dominant Frontotemporal Lobar Degeneration Due to the C9ORF72 Hexanucleotide Repeat Expansion: Late-Onset Psychotic Clinical Presentation - Galimberti, Daniela; Fenoglio, Chiara; Serpente, Maria; Villa, Chiara; Bonsi, Rossana; Arighi, Andrea; Fumagalli, Giorgio G.; Del Bo, Roberto; Bruni, Amalia C.; Anfossi, Maria; Clodomiro, Alessandra; Cupidi, Chiara; et al. (Biological psychiatry (1969), 2013)
A hexanucleotide repeat expansion in the first intron of C9ORF72 has been shown to be responsible for a high number of familial cases of amyotrophic lateral sclerosis or frontotemporal lobar degeneration (FTLD). Atypical presentations have been described, particularly psychosis. We determined the frequency of the hexanucleotide repeat expansions in a population of 651 FTLD patients and compared the clinical characteristics of carriers and noncarriers. In addition, we genotyped 21 patients with corticobasal syndrome, 31 patients with progressive supranuclear palsy, and 222 control subjects. The pathogenic repeat expansion was detected in 39 (6%) patients with FTLD (17 male and 22 female subjects); however, it was not detected in any corticobasal syndrome and progressive supranuclear palsy patients or controls. Twenty-four of 39 carriers had positive family history for dementia and/or amyotrophic lateral sclerosis (61.5%), whereas only 145 of 612 noncarriers had positive family history (23.7%; p<.000001). Clinical phenotypes of carriers included 29 patients with the behavioral variant frontotemporal dementia (bvFTD; 5.2% of all bvFTD cases), 8 with bvFTD/motor neuron disease (32% bvFTD/motor neuron disease cases), 2 with semantic dementia (5.9% of patients with semantic dementia), and none with progressive nonfluent aphasia. The presentation with late-onset psychosis (median age = 63 years) was more frequent in carriers than noncarriers (10/33 vs. 3/37, p = .029), as well as the presence of cognitive impairment at onset (15/33 vs. 5/37; p = .0039). The repeat expansion in C9ORF72 is a common cause of FTLD and often presents with late-onset psychosis or memory impairment.